Mastering Concurrent Computing through Sequential Thinking. - RAJSBAUM, SERGIO; RAYNAL, MICHEL (Communications of the ACM, 2020)
The article discusses concurrent computing via sequential thinking in information science and technology, particularly the difficulties associated with concurrent computing due to networking communications development and the inability to increase the speed of processors.